Effects of MnO2 addition on the microstructure and dielectric properties of LiTaO3 ceramics. (March 2020) - Yang, Wanwan; Zhang, Youfeng
Abstract: Lithium tantalite (LiTaO3 ) is an excellent single crystal. At present, only a few research studies have focused on polycrystalline LiTaO3 ceramics because it is beset with difficulties for the fabrication of dense ceramic by conventional sintering. In this study, LiTaO3 composite ceramics with added different MnO2 contents were obtained by hot-pressing sintering at 1300 °C. The sinterability, microstructure, and dielectric properties of LiTaO3 composite ceramics were investigated. The relative densities of the LiTaO3 composite ceramics are remarkably improved by the addition of the MnO2 powder. The LiTaO3 ceramic achieves the highest relative density (98.6%) and exhibits a homogeneous microstructure following the addition of 3 wt% MnO2 sintered in N2 . Only the LiTaO3 phase is observed at a MnO2 content addition below 3 wt%, and the secondary phase is found with further increases of added MnO2 (≥3 wt%) to the MnO2 /LiTaO3 (MLT) composite ceramics. The dielectric properties of the MnO2 /LiTaO3 composite ceramics are significantly influenced by the MnO2 contents, and the relatively optimal values are obtained when the addition of 3 wt% MnO2 sintered in N2 . Highlights: LiTaO3 matrix ceramics were successfully fabricated. The maximum relative density reaches 98.6%. Optimal properties are obtained at 3 wt% MnO2.